Numerical analysis of mass and heat transport in proton-conducting SOFCs with direct internal reforming. (1st July 2015) - Menon, Vikram; Banerjee, Aayan; Dailly, Julian; Deutschmann, Olaf
Highlights: Computationally efficient numerical model for H-SOFCs. Model is validated with two sets of experimental data for H2 O–H2 inlet mixtures. Novel electrochemical model to represent charge transfer. Temperature profiles, species transport, and electrochemistry are studied. The effect of anode zoning is investigated. Abstract: A computational model to investigate proton-conducting Solid-Oxide Fuel Cells (SOFCs) with direct internal reforming is developed. The numerical framework employs a 42-step elementary heterogeneous mechanism for Ni catalysts, using mean-field approximation. Mass transport through the porous media is described by the dusty gas model (DGM). Electrochemical parameters are deduced by reproducing two sets of experimental data, via the non-linear Butler–Volmer equation. A simple 1-D energy balance model is used to predict temperature profiles. The performance of the cell is analyzed by assuming the co-flow planar cell to be adiabatic. Simulations are carried out to understand the influence of various operating conditions on temperature distribution, species transport, and electrochemistry in the cell. The effect of dividing the anode into four zones, with different specific catalytic areas, on macroscopic performance parameters is investigated.